Irony on occasion : from Schlegel and Kierkegaard to Derrida and de Man - Newmark, Kevin, 1951- (Fordham University Press, 2012)
"What is it about irony--as an object of serious philosophical reflection and a literary technique of considerable elasticity--that makes it an occasion for endless critical debate? This book responds to this question by focusing on several key moments in German Romanticism and its afterlife in twentieth-century French thought and writing. It includes chapters on Friedrich Schlegel, Soren Kierkegaard, Friedrich Nietzsche, Thomas Mann, Jean Paulhan, Maurice Blanchot, Jacques Derrida, and Paul de Man. A coda traces the way unresolved tensions inherited from Romanticism resurface in a novelist like J.M. Coetzee. But this book is neither a historical nor a thematic study of irony. To the degree that irony initiates a deflection of meaning, it also entails a divergence from historical and thematic models of understanding. The book therefore aims to respect irony's digressive force by allowing it to emerge from questions that sometimes have little or nothing to do with the ostensible topic of irony. For if irony is the possibility that whatever is being said does not coincide fully with whatever is being meant, then there is no guarantee that the most legitimate approach to the problem would proceed directly to those places where "irony" is named, described, or presumed to reside. Rather than providing a history of irony, then, this book examines particular occasions of ironic disruption. It thus offers an alternative model for conceiving of historical occurrences and their potential for acquiring meaning."--Project Muse.